Childhood/Adolescent Pregnancies and Influenza Infections - Ahmet Gülen; Mustafa Hacımustafaoğlu (Güncel Pediatri)
In this article, we aimed to review child/adolescent pregnancies in general, and the clinical and epidemiological features including prevention and management of influenza in these patients in our country. World Health Organization (WHO) defines the children between 10-19 years as adolescents. In Turkey, the rate of marriage in adolescent children aged between 15-19 years is 9.3%. Of the births, 9% are in ages between 15-19 years and the rate of birth in ages between 15-19 years is 40/1000. The pre-birth health care of child/adolescent pregnancies is inadequate and the birth complications are higher than the normal pregnancies. The influenza infections in child/adolescent pregnancies are not different from the influenza infections in normal pregnancies, however it causes more severe diseases, higher rates of hospitalizations and higher mortality in pregnant women. During the pregnancy, influenza can affect mother, embryo or fetus as well as the newborn baby after the delivery. In pregnancy, the effects of influenza on embryo and fetus have not so far been extensively investigated. Transplasental viral transmission of the influenza is rare however it may cause birth defects. The clinical findings and diagnostic approaches in pregnancy are similar to normal population. Chemoprophylaxis or chemotherapy (oseltamivir or zanamivir) can be given to pregnant women when they are indicated for both influenza A or B. Vaccination is the preferred way of preventing influenza in pregnancy. Inactive influenza vaccine is safe and effective in every stage of pregnancy. Vaccination in pregnancy can prevent the mother, the fetus and the newborn baby up to 6 months from the complication of influenza. In Turkey the estimated vaccination rate in pregnancy is very low, which is less than 10%. (The Journal of Current Pediatrics 2014;1:31-6)